2022-RA-1347-ESGO The impact of the induction of anaesthesia and the opening of the abdominal cavity on haemodynamic parameters in cytoreductive debulking surgery. (20th October 2022) - Middel, Charlotte; Stetzuhn, Matthias; Sander, Nadine; Kalkbrenner, Björn; Tigges, Timo; Pielmus, Alexandru-Gabriel; Spies, Claudia; Pietzner, Klaus; Klum, Michael; Haefen, Clarissa von; Hunsicker, Oliver; Sehouli, Jalid; et al.
Abstract : Introduction/Background: High-risk surgery frequently is associated with haemodynamic instability leading to the administration of high amounts of intravenous fluids and catecholamines to stabilize cardiovascular function. The haemodynamic instability is commonly attributed to the inflammatory response related to surgical trauma. In this study, we investigated also, how the induction of anaesthesia and the opening of the abdominal cavity impact haemodynamics. Methodology: In a prospective, observational, monocentric study, haemodynamic measurements were obtained by the non-invasive methodology of thoracic electrical cardiometry (EC) in 29 patients with primary ovarian cancer undergoing multivisceral cytoreductive surgery. The change of haemodynamic parameters was analyzed from the day prior to surgery to the first intraoperative measurement by non-parametric longitudinal data analysis in a two-factorial experiment (dependent factor time). Results: Median age of patients was 59 [25-quartile 50; 75-quartile 61] years. 8 (28%) patients had a diagnosis of arterial hypertension, otherwise, no cardiovascular diseases were shown. The FIGO stages were in 22 (75%) patients above stage IIIc and 9 (31%) patients had more than 500 ml of ascites. The relative change from the baseline to the first intraoperative timepoint showed a reduced heart rate (HR, median -19 [25-quartile -26%; 75-quartile -10%]%, p<0.0001), stroke volume index (SVI, -9.5 [-15.3;3.2]%, p=0.0038), cardiac index (CI, -24.5 [-32;-13]%, p<0.0001) and the inotropic marker index of contractility (ICON, -17.5 [-35.3;-0.8]%, p<0.0001). Conclusion: Substantial changes in HR, SVI, CI, and ICON occurred from the day prior to surgery to the first intraoperative measurement, indicating that patients without relevant cardiovascular morbidity showed reduced cardiocirculatory flow and cardiac function. Furthermore, these data indicate that pharmacological modulation might optimize haemodynamic care during high-risk gynaecological surgery.